2013
DOI: 10.1021/jp3124814
|View full text |Cite
|
Sign up to set email alerts
|

Ceria Nanocubes: Dependence of the Electronic Structure on Synthetic and Experimental Conditions

Abstract: The properties of nanostructured ceria are both size- and shape-dependent. Here, ∼3–10 nm ceria nanocubes having exposed (002) surfaces were hydrothermally synthesized. For the first time, the electronic properties of such nanocubes were systematically studied using X-ray photoelectron spectroscopy and X-ray absorption spectroscopy. Comparisons of the collected Ce 3d XPS spectra after a single sweep revealed that the concentration of Ce3+ present within the nanocubes is independent of the particle size and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…It has been demonstrated previously that both Ce M 4,5 ‐edge XANES spectra and Ce 3d XPS spectra, which both result from the excitation of Ce 3d electrons, are highly sensitive to changes in the Ce oxidation state . This increased sensitivity is a result of the greater resolution of these spectra compared with the resolution of Ce L 3 ‐edge XANES spectra.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…It has been demonstrated previously that both Ce M 4,5 ‐edge XANES spectra and Ce 3d XPS spectra, which both result from the excitation of Ce 3d electrons, are highly sensitive to changes in the Ce oxidation state . This increased sensitivity is a result of the greater resolution of these spectra compared with the resolution of Ce L 3 ‐edge XANES spectra.…”
Section: Resultsmentioning
confidence: 97%
“…The reasons for the different features present in the spectra have been discussed in detail previously along with the method used to fit these spectra (see Fig. ); however, a short description is provided here . Eight peaks were used to fit the spectrum from CeO 2 , which may also contain traces of Ce 3+ because of surface defects.…”
Section: Resultsmentioning
confidence: 99%
“…This is due to the relatively simple preparation procedure coupled with their shape stability that allows characterization under various conditions. The structure of a CeO2 nanocube is a particle enclosed by six {100} faces with size ranging from a few nanometers 93 to more than 100 nm 76 . The ideal cubic structure is seldom shown in literature and more frequently nanocubes show round corners and edges which expose {111} and {110} surfaces, respectively ( Figure 7) 74 .…”
Section: Nanocubesmentioning
confidence: 99%
“…Specific to CeO 2 , previous studies have demonstrated that the electron beam acts in a reducing manner and drives the transition from Ce 4+ to Ce 3+ as reflected in EELS and high-resolution transmission electron microscopy (HRTEM) exit wave reconstruction measurements [1618]. It is worth noting that this effect is not limited to electron-based techniques, as any high energy radiation, such as X-rays, can also reduce CeO 2 [1921]. Therefore, the use of lower accelerating voltages and short probe dwell times to minimize beam damage further emphasizes the importance of efficient experimental design and aberration-correcting optics [7, 22].…”
Section: Introductionmentioning
confidence: 99%